A comparative study between supraclavicular brachial plexus block and Infraclavicular brachial plexus block for upper limb orthopedic surgeries: A prospective, randomized, double-blind study - Sarkar, Siddharth; Doshi, Shilpa Mitul (Bali Journal of Anesthesiology, 2019)
Introduction: Supraclavicular brachial plexus block is a common approach as it provides faster and dense blockade. In the past few years, infraclavicular brachial plexus block has become a method of increased interest as it has a lower complication rate and near to equal efficacy. The goal of this study was to compare block performance time, block characteristics, quality of block, patient’s satisfaction, and complications between infraclavicular and supraclavicular techniques for brachial plexus block.Patients and Methods: 100 subjects were randomized in a double-blind fashion, to receive either an infraclavicular block (Group I, n=50) or supraclavicular block (Group S, n=50) using nerve locator apparatus. Block performance time, onset, peak, duration of sensory and motor blockade, any change in hemodynamics, complications were recorded at scheduled intervals intra-operatively and post-operatively as per study protocol. Data were analyzed using GraphPad INSTAT version 3.06 software by Chi-square test or Mann-Whitney U test to compare categorical variables.Results: The block performance time was faster in the Group S compared to the Group I (4.8±4.4 minutes vs. 6.3±1.39 minutes, p <0.001). The sensory block onset time was faster in Group S compared to the Group I (6.9±1.58 minutes vs. 7.6±1.34 minutes, p=0.019). Other observed variables were considered statistically not significant.Conclusion: From our study, it is inferred that nerve locator guided Infraclavicular block by a vertical coracoid approach using multineurostimulation method is less rapidly executed as nerve locator guided supraclavicular block with a similar degree of surgical anesthesia and lesser complication rate.